Long-term evaluation of poly(Lactic acid) (PLA) implants in a horse: An experimental pilot study - Carvalho, Júlia Ribeiro Garcia [UNESP]; Conde, Gabriel [UNESP]; Antonioli, Marina Lansarini [UNESP]; Santana, Clarissa Helena; Littiere, Thayssa Oliveira [UNESP]; Dias, Paula Patrocínio; Chinelatto, Marcelo Aparecido; Canola, Paulo Aléscio [UNESP]; Zara, Fernando José. [UNESP]; Ferraz, Guilherme Camargo [UNESP] (MDPI, 2021)
In horses, there is an increasing interest in developing long-lasting drug formulations, with biopolymers as viable carrier alternatives in addition to their use as scaffolds, suture threads, screws, pins, and plates for orthopedic surgeries. This communication focuses on the prolonged biocompatibility and biodegradation of PLA, prepared by hot pressing at 180◦ C. Six samples were implanted subcutaneously on the lateral surface of the neck of one horse. The polymers remained implanted for 24 to 57 weeks. Physical examination, plasma fibrinogen, and the mechanical nociceptive threshold (MNT) were performed. After 24, 28, 34, 38, and 57 weeks, the materials were removed for histochemical analysis using hematoxylin-eosin and scanning electron microscopy (SEM). There were no essential clinical changes. MNT decreased after the implantation procedure, returning to normal after 48 h. A foreign body response was observed by histopathologic evaluation up to 38 weeks. At 57 weeks, no polymer or fibrotic capsules were identified. SEM showed surface roughness suggesting a biodegradation process, with an increase in the median pore diameter. As in the histopathological evaluation, it was not possible to detect the polymer 57 weeks after implantation. PLA showed biocompatible degradation and these findings may contribute to future research in the biomedical area.
Keywords: Biocompatibility; Biodegradation; Biomaterial; Polylactide-based materials; Polymer; Scanning electron microscopy